HUBUNGAN REALISASI TRANSFER DAU DAN DAK TERHADAP KESENJANGAN HORIZONTAL DI INDONESIA STUDY TERHADAP 33 PROVINSI PERIODE TA 2009-2013 - Deni Herdiyana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
The study was conducted to determine the relationship between the General Allocation Fund (DAU) and the Specific Allocation Fund (DAK) with the horizontal gap level (Gini Ratio). This study uses secondary data from various sources, including the Gini ratio taken from the BPS database while the realization of DAU and DAK transfers is taken from Audited Financial Statements (BUN BA-999.05) for the 2009-2013 FY Period by carrying out research tools through SPSS Statistics 23. This study results is that there is a strong relationship between the realization of DAU and DAK towards horizontal disparity, which is indicated by the Pearson Correlation figure which shows an increase from 0.316 in FY 2009 to 0.418 in FY 2013 for DAU, and an increase from 0.219 in FY 2009 to 0.316 in FY 2013 for DAK. Furthermore, a significant 2-tailed explanation shows that there is a stronger relationship between the DAU and the horizontal gap compared to the relationship between the DAK and the horizontal gap. The researcher recommends that the portion of the DAU allocation intended for people's welfare should be further improved and there is a need for further evaluation and supervision of the absorption of DAK by the Regional Government so that the implementation of the use of these funds is targeted and more accountable.